Breastfeeding Education in Term of Knowledge and Attitude through Mother Support Group - Lina Handayani; Azlina Mohd Kosnin; Yeo Kee Jiar (Journal of Education and Learning (EduLearn), 2012)
Knowledge and attitude are important factors for successful breastfeeding practice. The objective of this study was to examine the influence of knowledge and attitude on breastfeeding among Indonesian mothers who joined mother support group (MSG) program. This was a community based cross-sectional study. There were 221 mothers participated on this study. Multiple regression was used to asses the influence of knowledge and attitude on breastfeeding. Result of the study showed that knowledge and attitude influence breastfeeding practice.